Public transport governance in Greater Barcelona - Frederic Lloveras Minguell (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This paper describes the role of the Metropolitan Area of Barcelona (AMB) in the governance of public transport in Spain's second-largest agglomeration. It sets out how the AMB is able to provide integrated transport management, planning, financing and decision-making across different administrations and bodies of the Barcelona region, based on a mandate that comprises territorial planning, environment and sustainability, housing, economic development and social cohesion.
Keywords: 330